Immunostimulant and biocompatible gold and silver nanoparticles synthesized using the Ulva intestinalis L. aqueous extract. Issue 30 (10th July 2019) - González-Ballesteros, N.; Diego-González, L.; Lastra-Valdor, M.; Rodríguez-Argüelles, M. C.; Grimaldi, M.; Cavazza, A.; Bigi, F.; Simón-Vázquez, R.
Abstract : The biocompatibility properties of gold and silver nanoparticles synthesized by green chemistry. Abstract : This is the first study to report on the biocompatible and immunogenic properties of one-pot synthesised gold and silver nanoparticles (Au@UI and Ag@UI) using the macroalgae Ulva intestinalis (UI). The UI aqueous extract, Au@UI, and Ag@UI were obtained under sterile conditions and fully characterized by UV-vis spectroscopy, TEM, HRTEM, STEM and FTIR spectroscopy. Moreover, for the first time, the composition of carbohydrates in the UI extract has been reported along with the changes observed after nanoparticle synthesis by size exclusion chromatography, in order to investigate their possible role in the biosynthetic process. This study suggested that the polysaccharide fraction of the extract is involved in the formation and stabilization of the nanoparticles. The potential toxicity of the samples was evaluated using different cell lines and the hemocompatibility was tested in mouse erythrocytes. In addition, ROS production, complement activation and cytokine release were evaluated to determine the immunogenicity. The results showed that Au@UI and Ag@UI exhibit good biocompatibility and hemocompatibility, with the exception of Ag@UI nanoparticles at high concentration, which were hemolytic. The samples induced ROS release and complement activation, two key mechanisms in innate immunity. The samples also induced the release of cytokines from Th1 and Th2 profiles, and other cytokines implicated in the activation of the immune system. Au@UI and Ag@UI were biocompatible and preserved the immunostimulant properties of the UI extract. Hence, Au@UI and Ag@UI could be useful as adjuvants in vaccine development and promote a balanced Th1 and Th2 immune response mediated by ROS production, cytokine release and complement activation.